The Effect of Self-Efficacy, Perceived Organizational Support, and Organizational Commitments on Employee Organizational Citizenship Behavior at PT Surveyor Indonesia - Setyani Dwi Lestari; Muh. Taufik Hadi Saputra (Bina Nusantara University, 2022)
The research aims to analyze the effect of self-efficacy, perceived organizational support, and organizational commitment on organizational citizenship behavior of employees of PT Surveyor Indonesia (Persero) in Jakarta. The research used a survey method. The population was all permanent employees with total 437. With slovin formula, the number of samples obtained for this study is 82 respondents. The data were collected using questionnaire that distributed to the target samples using simple random sampling technique. All data will be tested for validity and reliability before continuing to analysis technique using multiple linear regression analysis. The results showed all variables have influence on organizational citizenship behavior at PT Surveyor Indonesia (Persero). Adjusted R2 0,965, meaning that 96,5% of organizational citizenship behavior can be explained by self-efficacy, perceived organizational support, and organizational commitment.